Graft function and renal protection with peritransplant systemic dexmedetomidine in kidney and liver recipients: systematic review and meta-analysis of randomized controlled trials - Reichert, Martin; Willis, Franziska; Koch, Christian; Amati, Anca-Laura; Braun, Jacqueline; Weigand, Markus A.; Sander, Michael; Karakizlis, Hristos; Schneider, Martin; Hecker, Andreas (International journal of surgery, 2025)
Background: - By modulating inflammatory pathways and exerting sympatholytic effects, perioperative dexmedetomidine offers several benefits in non-transplant surgery. Its favorable impact on ischemia-reperfusion injury and perioperative renal function supports the potential role of dexmedetomidine as an adjunct in transplant surgery. The evidence within various settings of kidney (KT) and liver transplantation (LT) is systematically reviewed. - Methods: - This systematic review evaluated randomized controlled trials investigating the efficacy of perioperative systemic dexmedetomidine in preventing allograft failure and/or kidney dysfunction in kidney and liver transplant recipients. Meta-analysis was performed using random or fixed effects model depending on the degree of statistical heterogeneity. Risk of bias and evidence quality were assessed. - Results: - Ten randomized controlled trials tested perioperative systemic dexmedetomidine in recipients of living (n = 3) or deceased donor (n = 1) kidney transplants and living (n = 5) or deceased donor (n = 1) liver transplants. With moderate to high certainty, cardiocirculatory, pulmonary, or surgical complication rates did not differ between dexmedetomidine and control groups. Risk for delayed graft function was reduced with dexmedetomidine after deceased donor KT (risk ratio: 0.52 [0.26-1.01]; P = 0.05) and living donor LT (risk ratio: 0.35 [0.17-0.74]; P = 0.006), though this did not translate into improved long-term allograft survival within limited long-term follow-up. Rates of posttransplant acute kidney injury were decreased following these transplant modalities (risk ratio: 0.40 [0.18-0.90]; P = 0.03 and 0.69 [0.50-0.95]; P = 0.02, respectively). Early postoperative serum creatinine was improved after KT and living donor LT. After living donor LT, serum parameters indicating allograft function improved with dexmedetomidine on postoperative days 1, 3, and 5. However, no such improvements were observed after deceased donor LT. - Conclusions: - Current evidence suggests that perioperative dexmedetomidine may reduce delayed graft function in deceased donor KT and living donor LT while supporting overall renal recovery. However, due to limited data and moderate certainty of evidence, further large-scale multicenter trials are needed to confirm clinical applicability and assess long-term efficacy.
Veröffentlicht: 12 June 2025
Gesehen am 19.01.2026